Germline BAP1 alterations in familial uveal melanoma. Issue 2 (26th October 2016) - Rai, Karan; Pilarski, Robert; Boru, Getachew; Rehman, Muneeb; Saqr, Ahmad H.; Massengill, James B.; Singh, Arun; Marino, Meghan J.; Davidorf, Frederick H.; Cebulla, Colleen M.; H. Abdel‐Rahman, Mohamed
Abstract : Uveal melanoma (UM) is the most commonly diagnosed primary intraocular tumor in adults. Familial UM (FUM), defined as two or more family members diagnosed with UM, is rare and estimated at less than 1% of all UM. Currently, BAP1 is the only gene known to contribute significant risk for UM. In this study we aimed to estimate the frequency of BAP1 mutation in FUM and to characterize the family and personal histories of other cancers in these families. We identified 32 families with FUM, including seven families previously reported by our group. BAP1 mutation testing was carried out by direct sequencing of the coding exons and the adjacent untranslated regions of the gene. Germline deletion and duplication analysis of BAP1 was assessed by multiplex ligation‐dependent probe amplification (MLPA). Germline BAP1 mutations were found in 6/32 (19%) families. No deletions or duplications were identified in any of the 24 samples tested by MLPA. Combined with published studies, the frequency of BAP1 mutations was 14/64 (22%) in FUM. FUM families without BAP1 mutations have distinct family histories with high rates of prostate cancer in first‐ and second‐degree relatives. It is likely that additional genes conferring risk for FUM exist. It is important to understand key shared features of FUM to focus future research on identifying these additional tumor predisposition syndromes. Though BAP1 should be tested first in these families, FUM families without BAP1 mutation should be explored for additional predisposition genes. © 2016 Wiley Periodicals, Inc.